2022
DOI: 10.1155/2022/8686670
|View full text |Cite
|
Sign up to set email alerts
|

Novel Design and Optimization of Porous Titanium Structure for Mandibular Reconstruction

Abstract: A porous material is considered to be a potential material that can be used to repair bone defects. However, the methods of designing of a highly porous structure within the allowable stress range remain to be researched. Therefore, this study was aimed at presenting a method for generating a three-dimensional tetrahedral porous structure characterized by low peak stress and high porosity for the reconstruction of mandibular defects. Firstly, the initial tetrahedral porous structure was fabricated with the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Although some studies have shown that muscle strength returns to presurgery levels during the healing period following resection [71,106], others suggest that reduced muscle force may occur due to decreased chewing power after reconstruction surgery [22,26,41]. We believe, this topic needs more investigation since there is still a lack of information about post-operative muscle forces in patients especially, those with extensive mandibular defects [48,74]. Upon further review, we also found that a considerable number of studies implemented a simplified model of the TMJ, primarily using fixed or hinge joint configurations as discussed before.…”
Section: D) Main Measurements In Feamentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies have shown that muscle strength returns to presurgery levels during the healing period following resection [71,106], others suggest that reduced muscle force may occur due to decreased chewing power after reconstruction surgery [22,26,41]. We believe, this topic needs more investigation since there is still a lack of information about post-operative muscle forces in patients especially, those with extensive mandibular defects [48,74]. Upon further review, we also found that a considerable number of studies implemented a simplified model of the TMJ, primarily using fixed or hinge joint configurations as discussed before.…”
Section: D) Main Measurements In Feamentioning
confidence: 99%
“…In conclusion, while using bony implants, especially fibular flaps, is regarded as the gold standard in larger reconstructions, there is some general dissatisfaction amongst patient populations in terms of functionality and aesthetics [62]. Therefore, alternative solutions such as prosthetic implants have been proposed [27,74]. Furthermore, autogenous grafts impact the patient even more since there are two points of surgical intervention.…”
Section: Analyzed Components 1) Definition Of Key Termsmentioning
confidence: 99%
“…Nevertheless, bone is a highly complex structure with different types of tissue (e.g., cortical or cancellous) and specific characteristics such as viscoelasticity and anisotropy [22,97], and simple modeling assumptions may not fully capture the intricate complexity of bone [95]. To account for this complexity, some studies [21] 2006 -✓ ---Tie et al [29] 2006 ✓ ----Schuller-Götzburg et al [30] 2009 ✓ ✓ --HA Wu et al (a) [31] 2012 ✓ ✓ ---Wong et al [23] 2012 --✓ --Jedrusik-Pawłowska et al [32] 2013 [33] 2013 -✓ --CI & PF Chang et al [34] 2013 [36] 2014 -✓ --CI & PF Bujtár et al [37] 2014 -✓ ---Narra et al [38] 2014 -✓ -CoT -Pinheiro and Alves [39] 2015 --✓ --Al-Ahmari et al [40] 2015 -✓ ---Jahadakbar et al [41] 2016 ✓ ✓ -CoT -Mehle et al [42] 2016 -✓ ---Park et al (a) [43] 2016 ✓ ✓ ---Dahake et al [44] 2017 --✓ --Nasr et al [45] 2017 -✓ ---Moiduddin et al (a) [46] 2017 [47] 2017 ✓ ✓ -FT -Luo et al [48] 2017 -✓ --RA Sanal et al [49] 2017 -✓ ---Seebach et al [24] 2017 ✓ ✓ ---Gutwald et al [50] 2017 -✓ -FT -Yoda et al [18] 2018 [52] 2018 ✓ ✓ ---Hoefert and Taier [53] 2018 -✓ ---Gao et al [ [64] 2021 ✓ ✓ ✓ --Koper et al [25] 2021 -✓ -CoT -Lang et al [22] 2021 ✓ ✓ -CoT & FT CA Kang et al [65] 2021 [74] 2022 --✓ --Shen et al [27] 2022 --✓ CoT -Jung et al [75] 2022 have adopted more sophisticated modeling techniques. Some of th...…”
Section: ) Static Analysismentioning
confidence: 99%
“…Underloading resorption, equilibrium, apposition, and overloading resorption are the four phases of bone remodeling, [31] 2012 -✓ -----Ti Jedrusik-Pawłowska et al [32] 2013 [36] 2014 -✓ ----✓ Ti Bujtár et al [37] 2014 ------✓ Ti Narra et al [38] 2014 -✓ -----Ti6Al4V ELI Al-Ahmari et al [40] 2015 -✓ -----Ti6Al4V ELI Jahadakbar et al [41] 2016 [67] 2021 In conclusion, while using bony implants, especially fibular flaps, is regarded as the gold standard in larger reconstructions, there is some general dissatisfaction amongst patient populations in terms of functionality and aesthetics [62]. Therefore, alternative solutions such as prosthetic implants have been proposed [27,74]. Furthermore, autogenous grafts impact the patient even more since there are two points of surgical intervention.…”
Section: Analyzed Components 1) Definition Of Key Termsmentioning
confidence: 99%
“…Based on previous studies [ 21 , 22 , 23 , 24 ], four structures with the same lattice size and different porosities were simulated to obtain the optimal lattice unit cell with a stronger bearing capacity. A functionally gradient scaffold optimization algorithm was proposed to control maximum stress and improve porosity, that is, a larger diameter is designed for high-stress struts and a smaller diameter for low-stress struts to reduce material wastage as much as possible while maintaining their performance.…”
Section: Introductionmentioning
confidence: 99%